Biofilm formation by bacteria isolated from intensive care units of a tertiary care hospital, with special relevance to its risk factors - Gogoi, Mayuri; Sharma, Ajanta (International Journal of Research in Medical Sciences, 2021)
Background: The purpose of this study was to detect biofilm formation by bacterial isolates from patients with device associated infection admitted in intensive care units (ICUs), to compare the three methods used for detection of bioiflm, to compare the antimicrobial susceptibility pattern of the biofilm producers with the non-producers and to study the risk factors associated with biofilm formation. Methods: A total of 115 bacterial isolates from patients with device associated infection admitted in different ICU for a period of one year was included in the study. These clinical isolates were detected for biofilm formation by tissue culture plate method, tube method and Congo red agar method. Kirby-Bauer disc diffusion method of antibiotic susceptibility was performed on all isolates. Results: Out of the 115 bacterial isolates, 71 were biofilm producers. Tissue culture plate method detected the maximum number of biofilm producers (61.7%). The maximum number of biofilm producers were isolated from tracheal aspirate and endotracheal tubes (52.1%) followed by blood (17%) and urine (12.6%) respectively. The predominant biofilm producing isolates were Klebsiella pneumoniae (39.4%), Staphylococcus aureus (19.7%) and Pseudomonas aeruginosa (16.9%). Multi drug resistance among the biofilm producers was significantly higher than the non-biofilm producers (p value=0.0125). The risk of biofilm formation was seen to increase with the increase in duration of hospital stay (p value=0.0092, statistically very significant). Conclusions: From this study it was found that a high degree of biofilm producers were isolated from patients on indwelling devices. Tissue culture plate was found to be the most accurate method. The degree of multidrug resistance among the bioiflm producers was significantly higher than the non-producers.